The Purification of Islamic Education System in Risalat an-Nur Perspective: A Case Study in Malaysia: [Pemurnian Sistem Pendidikan Islam Berdasarkan Metode Risalah An-Nur: Analisis Kajian di Negara Malaysia] - Nurulwahidah Fauzi (UIN Sunan Kalijaga Yogyakarta, 2014)
Ethnocentric concepts, theories and practices in education, predominantly embedded in western philosophy and values, tend to ignore the growing multicultural nature of educational institutions. In contrast, Islamic education and learning is an important aspect to develop of quality human capital and human resources development. Malaysia as a country in Southeast Asia that is developing as one of the strategic determinant in the economic, social, cultural international politics and applying the